Coating Inspection on Sea Transportation Equipment (Ship) Using Image Processing - Dianita Wardani; Agus Khumaidi; Rizal Fahmi; Imah Luluk Kusminah; Basuki Rahmat (Indonesian Journal of Innovation Multidisipliner Research, 2024)
Research in the last decade, particularly in this research there are methods and steps for completion, namely 4 process steps, including: First of all, take samples and image data from the parts of the ship that are being repaired and maintained, Then, in making the prototype tool resulting from the coating, it is assembled using several tools, mini PC is installed with a web camera, next the image for the observation further processes and processed using the edge method contours detection with the help of cany to obtain the contrast and contour from the ship's hull. For next process, uses Neural Network for image creation processes taken from prototype plating or plating on observed ship parts. Some mixed results from the process. The images taken areand thenthe data obtained is processed and its form is observedfor shape, pattern,corrosion, contour and so on layers formed. There are two classifications of RGB and GLCM results, the rejected results can match the corrosion spot found on the hull, and the accepted results mean no corrosion spot found.